A Green Synthetic Approach Towards One Pot Multi Component Synthesis of Hexahydroquinoline and 9‐Arylhexahydroacridine‐1, 8‐dione Derivatives Catalyzed by Sulphonated Rice Husk. Issue 48 (28th December 2020) - Dey, Sourav; Basak, Puja; Ghosh, Pranab
Abstract: An efficient, straight forward, eco‐friendly procedure for the synthesis of biologically active hexahydroquinoline derivatives and hexahydroacridine‐1, 8‐diones has been designed using a novel bio‐degradable heterogeneous catalyst, sulphonated rice‐husk (SRH). SRH provides high density of acid groups making it different from conventional solid acids containing single acid groups. We report an efficient protocol for the synthesis of hexahydroquinolines and hexahydroacridine‐1, 8‐diones using this carbon based acid catalyst (SRH) in solvent free and greener solvent respectively. Moreover, operational simplicity, greener reaction condition, reusability of the catalyst, excellent yield (upto 98 %) are the fundamental features of this protocol. The metal free catalyst was characterised using different spectroscopic techniques FTIR, SEM, EDX, Powder XRD, ICP‐AES. Abstract : An eco‐friendly procedure has been applied for the synthesis of biologically active hexahydroquinoline and hexahydroacridine‐1, 8‐diones derivatives using a novel bio‐degradable heterogeneous catalyst, sulphonated rice‐husk (SRH). SRH provides high density of acid groups making it quite different from conventional solid acids containing single acid groups. It is emerging as a efficient greener catalyst which can be a substitution of the previous methods containing toxic materials. Moreover, the catalyst is reusable up to several runs with slow decrease in its catalytic activity.